2013
DOI: 10.1038/bjc.2013.584
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cyclin-dependent kinase inhibitor devoid of ABC transporter-dependent drug resistance

Abstract: Background:Cyclin-dependent kinases (CDKs) control cell cycle progression, RNA transcription and apoptosis, making them attractive targets for anticancer drug development. Unfortunately, CDK inhibitors developed to date have demonstrated variable efficacy.Methods:We generated drug-resistant cells by continuous low-dose exposure to a model pyrazolo[1,5-a]pyrimidine CDK inhibitor and investigated potential structural alterations for optimal efficacy.Results:We identified induction of the ATP-binding cassette (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…[30,31,33,[37][38][39][40] We have previously reported the identification of severalCDK inhibitory compounds,includingamolecule selective for CDK7. [25,37,41] Here, we use acombination of structural, biophysical and modelling techniques to develop an understanding of the selectivity of representative inhibitors for CDK7 over CDK2. We have focused on three inhibitors from our compound library,t wo of which are CDK7 selective, and one which is CDK2 selective.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31,33,[37][38][39][40] We have previously reported the identification of severalCDK inhibitory compounds,includingamolecule selective for CDK7. [25,37,41] Here, we use acombination of structural, biophysical and modelling techniques to develop an understanding of the selectivity of representative inhibitors for CDK7 over CDK2. We have focused on three inhibitors from our compound library,t wo of which are CDK7 selective, and one which is CDK2 selective.…”
Section: Introductionmentioning
confidence: 99%
“…The first generation of CDK inhibitors has entered late-stage clinical trials but so far has only shown modest activity because of unfavorable pharmacology. 6 Most of the CDK inhibitors target the highly conserved kinase domain and could inhibit multiple CDK family members, which in part explain the undesirability of those trials. Hence, the identification of more selective and potent CDK inhibitors is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirms these mechanisms and extends these findings to breast cancer. This is the first study designed to investigate mechanisms of resistance to ICEC0942, although both ABCB1 and ABCG2 have been implicated in resistance to the pan-CDK inhibitor BS-194, a chemically-related precursor to ICEC0942 [40]. Our present study suggests that the structural differences between BS-194 and ICEC0942 have resulted in a reduced affinity of ABCG2 for ICEC0942 compared with BS-194.…”
Section: Discussionmentioning
confidence: 66%